Frontiers and hot topics in tumor metabolic reprogramming: a bibliometric analysis from 2014 to 2023 - Wen, Ping; Wang, Guanwen; Zhang, Ningning; Shao, Qing; Wang, Long; Qu, Fanli; Zeng, Xiaohua (Frontiers in Oncology, 2025)
IntroductionTumor metabolic reprogramming refers to the alteration of metabolic pathways and patterns by tumor cells to adapt to various environmental conditions and energy demands, thereby playing a pivotal role in tumor progression. Targeting tumor metabolism has been shown to exert anti-tumor effects and improve the efficacy of conventional cancer therapies. As a result, tumor metabolic reprogramming has become a research area of considerable clinical value and potential, warranting comprehensive investigation.MethodsThis bibliometric analysis was conducted to systematically summarize the research status, hotspots, and future trends in the field of tumor metabolic reprogramming. Relevant publications from January 1, 2014, to December 31, 2023, were retrieved from the Web of Science Core Collection. A total of 7,311 publications authored by 41,735 researchers from 5,967 institutions in 104 countries/regions were included. Bibliometric analysis and visualization were performed using VOSviewer, CiteSpace, and the bibliometrix R package.ResultsKeyword co-occurrence analysis revealed six major research clusters: tumor microenvironment, various cancers, pathological processes, major mechanisms, epigenetics, and mitochondria. The top three frequently occurring keywords were glycolysis, tumor microenvironment, and mitochondria. China was the most productive country (2,966 publications), followed by Fudan University as the most productive institution (216 publications), and Liu Yang as the most prolific author (40 publications).ConclusionResearch on tumor metabolic reprogramming has shown rapid global growth and demonstrates significant clinical importance and application potential, especially in the context of breast cancer..